Weibull distribution for determination of wind analysis and energy production - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2015)
In recent years, decreasing reserves and environmental problems related with fossil fuels have increased the demand for clean and renewable energy sources, as with all over the world and also in Turkey. Wind energy is the one of the most rapidly growing among the renewable energy sources in terms of technological and utilization. Turkey is one of the rich countries in Europe in respect to wind energy potential. Productive and effective use of this potential is very important for Turkey that is depended on foreign countries especially in respect to fossil energy sources. Wind speed values are the most important data in calculation of electrical energy from wind turbines. In this study, latest developments and energy-power equations related to wind turbines are investigated. Using of the data obtained from the wind measurement station installed in Sakarya-Esentepe region, annual electrical energy production of an example wind plant is predicted.
Keywords: Weibull distribution; Wind energy; Electrical energy production; Prediction